Pengembangan Model Pembelajaran Inkuiri-Seni Berbasis Google Art and Culture untuk Siswa Sma - Anisa Melianti; Eko Sugiarto (Syntax Corporation, 2023)
Appreciation learning has not taken place optimally with its delivery focusing more on understanding theory, involving less active student participation and using limited learning resources. Based on these conditions, it is considered necessary to develop an appreciation learning model, especially the appreciation of painting works using a more effective learning model. This development research aims to produce an inquiry-art learning model based on Google Arts and Culture. This research uses Research and Development (RnD) research approach. The subjects of this study were grade XI high school students in Kebumen Regency. Data collection techniques are carried out by observation, interviews and using questionnaires. The collected data was analyzed with a combination of qualitative Misdemeanors, Restorative Justice, Criminality and quantitative. The resulting product is in the form of a learning implementation plan, learning model syntax, and student activity sheets. The results of the study obtained showed that the development of learning models applied to grade XI high school students showed that students were more enthusiastic and actively involved in the learning process, compared to previous learning. The ability of students to respond in discussion activities and through painting appreciation worksheets is proven to be good, so that the Google Arts and Culture-based inquiry-art learning model is feasible to be applied in appreciation learning in schools.